2022
DOI: 10.1186/s13287-022-02741-2
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphic regeneration of the mouse digit tip is finite

Abstract: Background Structural regeneration of amputated appendages by blastema-mediated, epimorphic regeneration is a process whose mechanisms are beginning to be employed for inducing regeneration. While epimorphic regeneration is classically studied in non-amniote vertebrates such as salamanders, mammals also possess a limited ability for epimorphic regeneration, best exemplified by the regeneration of the distal mouse digit tip. A fundamental, but still unresolved question is whether epimorphic rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…While all digits progress through all stages, the rate of stage progression was variable even between digits from the same animal. Although previous studies have traditionally investigated digit regeneration on the basis of time, that is, DPA, 11,17,23,25,26 our findings show that categorising the initial phases of digit regeneration by stage greatly diminishes the variability between digit samples with respect to changes in bone volume and length, as well as cell proliferation, osteoclastogenesis, osteoclast activity and spatial osteogenic differentiation. Importantly, visualising the P3 bone via micro CT staging provides a means to estimate open versus closed digit wounds.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…While all digits progress through all stages, the rate of stage progression was variable even between digits from the same animal. Although previous studies have traditionally investigated digit regeneration on the basis of time, that is, DPA, 11,17,23,25,26 our findings show that categorising the initial phases of digit regeneration by stage greatly diminishes the variability between digit samples with respect to changes in bone volume and length, as well as cell proliferation, osteoclastogenesis, osteoclast activity and spatial osteogenic differentiation. Importantly, visualising the P3 bone via micro CT staging provides a means to estimate open versus closed digit wounds.…”
mentioning
confidence: 59%
“…In addition, anatomical staging of the bone stump is a method to identify the timing of wound closure. Thus, while micro CT analysis has long been utilised to investigate P3 bone regeneration, 11,13–17,22–26,30–34 the current study demonstrates that visualising the bone via micro CT staging also provides a means to infer the state of the radiolucent soft tissue (e.g. cell proliferation and wound closure).…”
Section: Discussionmentioning
confidence: 83%
“…21 Compared to amphibians with extraordinary regenerative capacity, data suggest the lack of regenerative capacity in mammals may come from a desynchronization of the fine-tuned interplay of progenitor cells such as blastema and differentiated cells. 22,23 In mice, the response to amputation is specific to the level: cutting through the distal third of the terminal phalanx elicits a regeneration response, yielding a new digit tip resembling the lost one, while an amputation through the distal third of the intermediate phalanx triggers a wound healing and scarring response. 24 Wound Healing Following Limb Amputation Limb amputation represents a profound change in an individual's life, impacting daily activities and overall well-being.…”
Section: U T I S D O N O T C O P Ymentioning
confidence: 99%
“…For instance, aging slows the ability of the blastema to differentiate into bone such that old mice require an additional month of regeneration as compared to young mice controls ( Brunauer et al, 2021 ). It was also shown that repeated amputation of the same digit tip reduced the number of osteoblasts and proliferative index of the blastema, which ultimately led to less bone regeneration ( Dolan et al, 2022b ). This finding suggests that multiple amputations negatively impact the overall ability of the blastema to differentiate into bone.…”
Section: Connective Tissue and Extracellular Matrix During Regenerationmentioning
confidence: 99%